ANALISIS PENGARUH STRATEGI PENGEMBANGAN PRODUK KECAP BANGO RASA MANIS PEDAS GURIH TERHADAP LOYALITAS KONSUMEN PADA KECAP BANGO PRODUKSI PT. UNILEVER INDONESIA DI KOTA SEMARANG - Th. Susetyarsi (STIE Pelita Nusantara Semarang, 2013)
This study aims at finding (1) the extent of partial influence of developmental stategy of Bango soy sauce product with sweet, spicy, savory flavors in the form of product quality, flavor, and packing towards consumer loyalty at PT. Unilever Indonesia Semarang City, and (2) the extent of simultaneous influence of developmental stategy of Bango soy sauce product with sweet, spicy, savory flavors in the form of product quality, flavor, and packing towards consumer loyalty at PT. Unilever Indonesia Semarang City.The population of the study were the customers who used Bango soy sauce product with sweet, spicy, savory flavors produced by PT. Unilever Indonesia Semarang City, the number of which was not exactly determined. The data were collected from 100 respondents by using questionnaire. The hypothesis testing and the conclusion were done by using multiple regression analysis, determination coefficience (R2), partial testing with T-test, and simultaneous testing with F-test.Multiple regression analysis shows that the independent variables have positive influence on the dependent variables. The R2 value is 0.86 meaning that the independent variables have 86% positive influence on the dependent variables and 14% are influenced by the other variables outside the model.Both partial and simultaneous testings support H1 and H2 hypotheses, that is, the product development consisting of product quality (X1), product flavor (X2), and product packing (X3) has significantly partial and simultaneous influence on customer loyalty to the products of PT. Unilever Indonesia Semarang City. The analysis also shows that variable of product flavor (X2) has the highest influence on the customer loyalty.